Peranan Pemerintah Daerah Dalam Pemberdayaan Masyarakat - Lasiman Sugiri (PUBLICA, 2012)
This article highlights role of it's the local government and his staff in executing duty or function of community empowerment, including identifying supporter factor and community empowerment process resistor. Community empowerment intended focused at various aspects related to life public as nation community, that is empowerment in educational, economics, culture social, psychology, and politics. Community empowerment is absolutely has to be done, and every its the local government and his staff must stand is big poweredness member of his its, especially stimulates, pushs, or motivates every individual to have ability or powered to determine what becoming its the life choice. Local government role (govern or Regent, or Mayor, and area his staff) meant to increase strength from public weakness, or preparation to public in the form of resources, opportunity, knowledge, and expertise to increase public itself capacities in determining their future, and to be able to participate and influences life of community society itself in area.